Reproducing the South: William Faulkner, pregnancy and the contemporary US novel - Hamilton, Katie (2018)
This thesis identifies pregnancy as an overlooked but significant motif in Faulkner's work which develops his major themes of southern blood politics and white supremacy, as well as the role of aesthetic production and the writer in a rapidly modernizing world. It argues that, although the major studies of Faulkner's female characters do not discuss the significance of pregnancy in this work, contemporary US writers have found the theme a significant source of inspiration. It examines how these novelists are re-writing Faulkner's pregnant characters to engage with debates about southern literary genealogies, Faulkner’s role in shaping cultural representations of the contemporary South, as well as his place in the American canon more generally. The first chapter draws out the importance of pregnancy to some of the most significant themes Faulkner re-examines so obsessively across his major novels of the 1930s. The subsequent three chapters reveal how seemingly disparate contemporary novelists – including Larry Brown, Jesmyn Ward, Suzan-Lori Parks and Jayne Anne Philips – are producing novels which focus on characters who are recognizable re-inscriptions of Faulkner’s pregnant protagonists, in sustained interrogations of Faulkner's place in the literary heritage that shapes their writing. In doing so, this thesis contributes to the ongoing critical debate concerned with the nature and extent of Faulkner's continued influence over contemporary literature, and demonstrates that his work continues to be a generative topic for today's novelists, even as the world they write about becomes increasingly removed from Yoknapatawpha.